Implementation of Android-Based English Conversation Educational Game Using MDLC Method - Akbar Iskandar; Giri Artoyo; Saltanat Meiramova; Makhabbat Ramazanova (Jurnal Abdimas Cendekiawan Indonesia, 2025)
Many Indonesian students face significant challenges in learning English, particularly in speaking skills. Despite early exposure to English in schools, active speaking remains a struggle for many learners. The advancement of technology has opened new opportunities for educational innovation, including the use of educational games as engaging and interactive learning media. This study aims to develop an Android-based educational game that focuses on improving English conversation skills using the Multimedia Development Life Cycle (MDLC) method. The game is specifically designed to assist school children who experience difficulties in basic English speaking. Through an interactive and enjoyable approach, this game is expected to enhance students' learning motivation, strengthen their vocabulary acquisition, and improve their ability to construct simple sentences. The research follows six stages: concept, design, material collection, assembly, testing, and distribution. Black box testing results indicate that all menu functions and interactive features operate correctly, providing users with seamless access to tutorials, level-based challenges, and an engaging assessment system. This educational game serves not only as an alternative learning tool but also as a means to improve English literacy among students. By integrating gamified learning, the application fosters an immersive and enjoyable learning experience, contributing to more effective English language acquisition. Ultimately, this innovation has the potential to support students' communication skills, increase their confidence in using English, and contribute to the broader goal of enhancing English proficiency in Indonesia.